Association between preoperative frontal electroencephalogram alpha asymmetry and postoperative quality of recovery: an observational study. (April 2023) - Bae, Jayyoung; Lee, Jun Sung; Oh, Jooyoung; Han, Dong Woo; Jung, Heejae; Kim, Seok-Mo; Song, Young
Abstract: Background: Left-sided frontal alpha asymmetry on electroencephalograms, which indicates decreased relative left-hemispheric activity, has been associated with depression, anxiety, and stress responsivity. We aimed to evaluate the association between perioperative measures of frontal alpha asymmetry and quality of recovery (QoR) after surgery. Methods: We enrolled 110 female patients undergoing thyroidectomy and recorded perioperative electroencephalograms. The power of the prefrontal alpha band (8–13 Hz) was measured in the Fp1 and Fp2 leads. Left-sided frontal alpha asymmetry was defined as a higher alpha band power in Fp1 than in Fp2 and vice versa. QoR was assessed using the QoR-15 score on the day before surgery and postoperative days 1 and 2. The primary study endpoint was a difference in postoperative global QoR-15 score between preoperative left-sided and right-sided alpha asymmetry groups. The predictability of frontal alpha asymmetry for poor QoR-15 score was also evaluated. Results: The global QoR-15 score showed a significant group-by-time interaction, and post-hoc analysis revealed significantly lower scores on postoperative days 1 (P=0.006) and 2 (P<0.001) in the left-sided frontal alpha asymmetry group. In the multivariate logistic regression analysis, preoperative left-sided frontal alpha asymmetry was associated with a 3.3-fold increased risk of the lowest tertile for the postoperative day 1 QoR-15 score (95% CI: 1.31–8.24; P=0.011). Conclusions: Preoperative left-sided frontal alpha asymmetry was independently associated with a lower postoperative QoR-15 score in female patients undergoing thyroidectomy, highlighting the potential role of preoperative frontal electroencephalography in predicting patient-centred outcomes after surgery. Clinical trial registration: KCT0006586 (http://cris.nih.go.kr/ ).